Analysis metodology of the character in the fiction poscast: case study (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2023)
The main objective of this paper is to propose a methodology to analyze the characters in radio fiction, based on the updating of previous methodologies of audiovisual narrative and its adaptation to the medium and radio language. This methodology is applied in a specific case study: the serial “Negra y Criminal”, directed by Mona León Siminiani (Cadena Ser, Podium Podcast, 2016-2019). The aim is to evaluate the effectiveness of the methodology and to explore the resources used to create characters in this production. A methodology for the analysis of the radio character is proposed based on the method by Casetti and Di Chio (2007), adapted for the radio medium by Guarinos (2009). The main conclusion is that radio dramatic fiction can afford the creation of round, complex characters, with dimensionality and volume. The fictional radio character can be studied from the perspective of audiovisual narrative, considering the nature of the medium in which it will develop. As a particularity would remain its articulation from a single raw material: the sound and its wide variety of expressive resources. This determining factor becomes especially notable in the recreation of the physical materiality of the character.
Keywords: Radio; Radio Fiction; Podcast; Radio Script; Audio-visual Analysis